Evaluation of yam host-plant response to rootknot nematodes in Uganda - Mudiope, J.; Speijer, P.R.; Maslen, N.R.; Adipala, E. (1998)
A field trial was established at Sendusu. 40 km north of Kampala. Uganda, to evaluate the response of yarn lines, developed by the International Institute of Tropical Agriculture (IITA), to nematode infestation. The field was naturally infested with nematodes and plants were established from tissue culture. Harvested yam tubers were infested mainly with Meloidogyne javanica and, to a lesser extent, with Pralylenchus spp.; Scutonel/onema sp., Rolylenchulus sp. and HelicOlylenchus sp. were round occasionally. Line TOR 87/00559 OP (38) supported the highest population 01 M javanica juveniles, while lines TDR 87/00571 OP {71} and TDR 91/00121 OP {22} did not support any nematode species, suggesting the existence 01 resistance to root•knot nematodes in the IITA germplasm collection.